Pengaruh Citra Perusahaan, Prosedur Kredit, dan Jaminan Kredit terhadap Keputusan Pelaku UMKM dalam Melakukan Kredit pada Lembaga Keuangan Bukan Bank di Kecamatan Buleleng - Putri, Luh Giantini; Putu Eka Dianita Marvilianti Dewi (Vokasi : Jurnal Riset Akuntansi, 2022)
This study aims to determine the effect of corporate image, credit procedures, and credit guarantees on the decision to make credit. This research is a type of quantitative research with the number of respondents as many as 80 formal MSMEs actors registered at the Department of Trade, Industry, Cooperatives and UMKM in Buleleng Regency who have made credit loans to Non-Bank Financial Institutions. Data were obtained by distributing questionnaires directly to formal MSMEs in Buleleng District. The sample was selected using criteria with purposive sampling technique, then questionnaires were distributed as many as MSMEs that met the criteria only. The data used is primary data in the form of respondents' answers and processed using SPSS version 22. The data test instrument used in this study was a data quality test consisting of validity and reliability tests. After that, the classical assumption test consists of normality test, multicollinearity test, and heteroscedasticity test. The hypothesis testing used is the t test and the coefficient of determination. The data were analyzed using multiple linear regression analysis method. The results of this study indicate that the company's image, credit procedures, and credit guarantees partially have a positive and significant effect on the decision to make credit.